Evaluación del cumplimiento de los elementos de control en las transacciones y operaciones Business to Business to Consumer to Consumer (B2B2C2C) (2023)
In view of the notable rise of e-commerce and B2B2C2C business models, the central purpose of this article is to provide a detailed description of how they work, examine in detail the components that must be taken into account when carrying out an audit and evaluate compliance with the elements subject to control in Business to Business to Consumer to Consumer transactions and operations.